Regulation of Proliferation by a Mitochondrial Potassium Channel in Pancreatic Ductal Adenocarcinoma Cells - Peruzzo, Roberta; Mattarei, Andrea; Romio, Matteo; Paradisi, Cristina; Zoratti, Mario; Szabò, Ildikò; Leanza, Luigi (Frontiers in Oncology, 2017)
Previous results link the mitochondrial potassium channel Kv1.3 (mitoKv1.3) to the regulation of apoptosis. By synthesizing new, mitochondria-targeted derivatives (PAPTP and PCARBTP) of PAP-1, a specific membrane-permeant Kv1.3 inhibitor, we have recently provided evidence that both drugs acting on mitoKv1.3 are able to induce apoptosis and reduce tumor growth in vivo without affecting healthy tissues and cells. In the present article, by exploiting these new drugs, we addressed the question whether mitoKv1.3 contributes to the regulation of cell proliferation as well. When used at low concentrations, which do not compromise cell survival, both drugs slightly increased the percentage of cells in S phase while decreased the population at G0/G1 stage of cells from two different pancreatic ductal adenocarcinoma lines. Our data suggest that the observed modulation is related to ROS levels within the cells, opening the way to link mitochondrial ion channel function to downstream, ROS-related signaling events that might be important for cell cycle progression.